2008
DOI: 10.1179/174313408x259445
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Velamentous Cord Insertion and Vasa Praevia using Ultrasound and Magnetic Resonance Imaging - A Case Report

Abstract: Velamentous insertion of the cord is defined as insertion of the umbilical cord into membranes before it enters the placenta. It occurs in 1% of singleton pregnancies. Vasa praevia occurs when the amniotic membrane with the velamentous vessels covers the cervical os. Its incidence is 1/2000 to 1/3000 but when it happens prenatal mortality is between 30%-100% from rupture of vessels and fetal exsanguination. Prenatal diagnosis and early delivery by Caesarean section at 36 weeks improve fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Marginal cord insertion, also called battledore placenta, is when the cord inserts within 3 cm of the edge of the placental mass. VCI, also known as membranous cord insertion, is defined as “insertion of the umbilical cord into membranes before it enters the placenta.” 7 There are two theories on the pathogenesis of VCI. The first states that the cord implants into the trophoblast of the decidua capsularis rather than the trophoblast that forms the placental mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marginal cord insertion, also called battledore placenta, is when the cord inserts within 3 cm of the edge of the placental mass. VCI, also known as membranous cord insertion, is defined as “insertion of the umbilical cord into membranes before it enters the placenta.” 7 There are two theories on the pathogenesis of VCI. The first states that the cord implants into the trophoblast of the decidua capsularis rather than the trophoblast that forms the placental mass.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5 A VCI, also called a membranous cord insertion, is when the umbilical cord inserts into the membranes rather than directly into the placental mass and the umbilicus vessels course through the membranes unprotected by the umbilical cord or Wharton jelly. 6,7 This condition is present in 1.5% of singleton pregnancies and 6% of multiple-gestation pregnancies. 6 The more common variation of type 1 vasa previa is when the placental mass is in the lower uterine segment and the VCI is over or close to the internal cervical os.…”
mentioning
confidence: 99%
“…49 While ultrasound has been suggested to be the most effective diagnostic tool for antenatal diagnosis of VP, some authors have also suggested that Magnetic Resonance Imaging (MRI) may be useful. [50][51][52][53] While there may be some recognised benefits of MRI in providing additional information to both grey-scale and colour Doppler sonography such as greater detail of vessel location prior to CS and further confirmation of the placental forms (e.g. single, placenta praevia, bilobed, succenturiate lobe) when used during the third trimester, 50,52 the cost and extra time required is generally prohibitive.…”
Section: Timing Of Ultrasound Diagnosismentioning
confidence: 99%